1998
DOI: 10.1111/j.1524-4725.1998.tb00013.x
|View full text |Cite
|
Sign up to set email alerts
|

Tie-over Bolster Dressings May Not Be Necessary to Secure Small Full Thickness Skin Grafts

Abstract: We have found tie-over bolster dressings and basting sutures to be unnecessary in our series of small FTSG. This technique saves time and material and minimizes handling of the graft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 11 publications
0
32
0
Order By: Relevance
“…Once all sutures are in place, ointment is applied to the graft site, and a nonadherent material, such as Telfa, is placed over the graft and the immediate surrounding skin. A bolster dressing is then typically applied to further protect and immobilize the graft; however, some surgeons dispute this need 39,40. The tie‐over bolster is the classic dressing for FTSGs in which individual sutures are used to secure a pressure dressing over the graft.…”
Section: Full‐thickness Skin Graftsmentioning
confidence: 99%
“…Once all sutures are in place, ointment is applied to the graft site, and a nonadherent material, such as Telfa, is placed over the graft and the immediate surrounding skin. A bolster dressing is then typically applied to further protect and immobilize the graft; however, some surgeons dispute this need 39,40. The tie‐over bolster is the classic dressing for FTSGs in which individual sutures are used to secure a pressure dressing over the graft.…”
Section: Full‐thickness Skin Graftsmentioning
confidence: 99%
“…Bolster dressings were not used for skin graft repairs, as data have suggested that they may not be necessary to secure full-thickness skin grafts to reduce the chance of graft necrosis. 15,16 Also, attention was given to the previously reported adverse relationship between tobacco use and the outcome of cutaneous surgical procedures. 17 To minimize the potential development of tissue necrosis in our patients, we requested that patients limit cigarette smoking and the use of other tobacco products for 1 week before surgery and for the immediate postoperative period (1-2 weeks).…”
Section: Methodsmentioning
confidence: 99%
“…Blind placement of a basting suture may nick a blood vessel in the wound base, leading to hematoma or seroma. Additionally, if the bolster provides too much pressure, the blood supply to the graft may be compromised leading to graft loss (31,32). Compression dressings, basting sutures, and bolsters are no substitute for meticulous intraoperative hemostasis.…”
Section: Causes Of Tissue Ischemia – Before During and After Surgerymentioning
confidence: 99%